The Characteristics Model, Hedonic Prices, and the Clientele Effect - Jones, Larry E. (Journal of Political Economy, 1988)
In this paper, the characteristics model of Lancaster is reconsidered. It is shown by example that equilibrium prices need not be linearly decomposable. It does follow that equilibrium prices must be a convex function of characteristics, however. Further, it is shown that this fact holds independent of the form of firm competition (e.g., perfect or monopolistic). Finally, the predictions of the theory are discussed in the context of two empirical examples.